2012
DOI: 10.1590/s1516-14392012005000008
|View full text |Cite
|
Sign up to set email alerts
|

Improvement compressive strength of cementitious composites in different curing media by incorporating ZrO2 nanoparticles

Abstract: In the present work, the effect of curing medium on microstructure, physical, mechanical and thermal properties of ZrO 2 nanoparticles blended concrete has been investigated. ZrO 2 nanoparticles were partially used instead of cement by 0.5, 1.0, 1.5 and 2.0 weight percent. Curing of the specimens was carried out in water and saturated limewater for 7, 28 and 90 days. The results indicate that ZrO 2 nanoparticles up to maximum of 2.0% produces cementitious composite with improved compressive strength by curing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Therefore, the hydration of cement is accelerated; generating large volumes of hydration products, increasing the packing density of the cement particles and reducing the volume of large pores in the cementing paste [17,18]. It has also been found that the increase in the percent volume fraction of zirconium oxide nanoparticles decreases the initial and final setting time of the concretes, indicating that zirconium oxide nanoparticles have a higher hydration reaction rate than cement, since they are characterized by unique surface effects, smaller particle sizes, and higher surface energy [18,19]. It has also been reported that the workability of mortar or concrete mixtures decreases with the increasing of zirconium oxide nanoparticle content [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the hydration of cement is accelerated; generating large volumes of hydration products, increasing the packing density of the cement particles and reducing the volume of large pores in the cementing paste [17,18]. It has also been found that the increase in the percent volume fraction of zirconium oxide nanoparticles decreases the initial and final setting time of the concretes, indicating that zirconium oxide nanoparticles have a higher hydration reaction rate than cement, since they are characterized by unique surface effects, smaller particle sizes, and higher surface energy [18,19]. It has also been reported that the workability of mortar or concrete mixtures decreases with the increasing of zirconium oxide nanoparticle content [20].…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned studies analyzed the problem qualitatively and provided valuable structural designs as well as empirical safety factors. In addition, many studies on improving the toughness and compressive strength of ceramic materials have been carried out [16,17]. However, there is still a lack of theoretical studies concerning the calibration of the tensile stress on the ceramic shell end faces.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 showing the chemical and physical properties of Portland Cement has been duplicated in later publications [2][3][4] (among others) with no reference to this article; Figures 2 and 3 appear identical to those published in [5,6]; Figure 2 has similarities with Figure 2 in [3] when rotated, despite representing different nanoparticles; Figure 7a has similarities with Figure 8(2)a of [7] and Figure 3a of [8]; and Table 7 has been partially reproduced in Table 6 of [9] without any cross-reference.…”
mentioning
confidence: 99%